2010
DOI: 10.1007/s10566-010-9102-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Perceived Needs and Barriers of Youth Offenders Preparing for Community Reentry

Abstract: This study explored how gender differences may influence the community reentry experiences of incarcerated youth. Structured surveys assessing risk factors for re-offending, perceived reentry needs, and anticipated barriers to meeting these needs were administered to a convenience sample of males (n = 36) and females (n = 35) who were within 60 days of release from two probation camps in Southern California. Bivariate analyses found significant gender differences in prior risk factors, educational aspirations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…Traffickers also manipulated CSEY by playing the role of a boyfriend/friend, mandating debt repayment, or commanding loyalty after forcing the survivor to commit a crime (Reid, 2014). Lacking confidence regarding school and independent living skills can further perpetuate the perceived need to continue sex work (Fields & Abrams, 2010).…”
Section: Challenges To Commercial Sexual Exploitation Exitmentioning
confidence: 99%
“…Traffickers also manipulated CSEY by playing the role of a boyfriend/friend, mandating debt repayment, or commanding loyalty after forcing the survivor to commit a crime (Reid, 2014). Lacking confidence regarding school and independent living skills can further perpetuate the perceived need to continue sex work (Fields & Abrams, 2010).…”
Section: Challenges To Commercial Sexual Exploitation Exitmentioning
confidence: 99%
“…Research has suggested that there is a need to identify risk factors and barriers to successful community reentry into in order to support youth areas they are most vulnerable (Fields and Abrams 2010). Ongoing transitional supports such as individualized transition plans, school supports, vocational training, and therapeutic interventions are critical to the successful community adaption of these children and youth (Casey et al 2010;Fields and Abrams 2010;Frensch et al 2009). The third option for consideration may be that intensive residential treatment is an inappropriate option for the needs of this identified high-risk group.…”
Section: Implications For Treatmentmentioning
confidence: 99%
“…Many become re-exposed to home or neighbourhood violence, heightening the chances of recidivism and adverse health outcomes 18. Most incarcerated youth express plans to reform, but successful transitions require multiple levels of support – support that systems of care often fail to provide 22. Studies have found that up to 75% of released adolescents are re-arrested within 3 years 23.…”
Section: Introductionmentioning
confidence: 99%